2014
DOI: 10.1007/s10067-014-2738-4
|View full text |Cite
|
Sign up to set email alerts
|

Can procalcitonin be used to distinguish between disease flare and infection in patients with systemic lupus erythematosus: a systematic literature review

Abstract: Distinction between infection and febrile disease flare in patients with systemic lupus erythematosus (SLE) is fundamental but often difficult to make, because clinical presentation can be similar. A systematic review of all articles indexed in PubMed through October 2013 was performed, in order to examine the potential role of procalcitonin (PCT) for the discrimination between SLE flare and infection. Among the 12 papers identified, 5 articles reported on PCT levels in SLE patients without infection, 6 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…We also showed that compared to PCT, CRP is a more sensitive and speci c marker for diagnosing bacterial infections in SLE [41]. However, there had also been some reports that PCT is more speci c and has better diagnostic accuracy than CRP for infection in SLE [15,33,42]. Combination of these eight parameters resulted in a model with calculated AUC of 0.7886 and with sensitivity of 63.5% and speci city of 89.2% (Fig.…”
Section: Parameters Predictive Of Acute Infectionmentioning
confidence: 65%
See 2 more Smart Citations
“…We also showed that compared to PCT, CRP is a more sensitive and speci c marker for diagnosing bacterial infections in SLE [41]. However, there had also been some reports that PCT is more speci c and has better diagnostic accuracy than CRP for infection in SLE [15,33,42]. Combination of these eight parameters resulted in a model with calculated AUC of 0.7886 and with sensitivity of 63.5% and speci city of 89.2% (Fig.…”
Section: Parameters Predictive Of Acute Infectionmentioning
confidence: 65%
“…Limited information is available regarding plasma PCT levels in patients with active SLE. Patients with active SLE may have slightly increased PCT levels [15,18]. However, Garvand et al noted an unusual phenomenon PCT levels were high during macrophage activation syndrome (MAS) episodes in lupus ares [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A review of the literature published until 2014 indicated that raised PCT levels ≥0.5 μg/L should strongly suggest bacterial infection in the context of SLE. 20 However, there is limited data regarding the diagnostic accuracy of PCT in case of hemophagocytic syndrome, a severe condition which can mimic or complicate both lupus flare and infection. Another study suggests the use of the delta neutrophil index (DNI), which reflects the fraction of peripheral blood immature granulocytes, to differentiate infection from SLE flare.…”
mentioning
confidence: 99%
“…Чувствительность и специфичность ПКТ состав-ляли 93,1 и 78,6 % соответственно. По данным I. Serio и соавт., среднее значение ПКТ у пациентов с почеч-ной недостаточностью было несколько выше, О б з о р ы чем в отсутствие последней, но не превышало поро-говых значений [32].…”
Section: системная красная волчанкаunclassified